1991
DOI: 10.2165/00003495-199141030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone

Abstract: Mitoxantrone is a dihydroxyanthracenedione derivative which as intravenous mono- and combination therapy has demonstrated therapeutic efficacy similar to that of standard induction and salvage treatment regimens in advanced breast cancer, non-Hodgkin's lymphoma, acute nonlymphoblastic leukaemia and chronic myelogenous leukaemia in blast crisis; it appears to be an effective alternative to the anthracycline component of standard treatment regimens in these indications. Mitoxantrone is also effective as a compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(49 citation statements)
references
References 309 publications
0
47
0
2
Order By: Relevance
“…It demonstrated therapeutic efficacy in the treatment of a wide range of solid tumours, such as breast cancer, and haematological malignancies [1]. Based on beneficial results from the experimental allergic encephalomyelitis (EAE) animal model of multiple sclerosis (MS), where mitoxantrone suppressed relapses and lesions 10–20 times more effectively than cyclophosphamide [5, 6, 7], pilot studies showed positive effects on relapse and progression rate in heterogeneous groups of patients who had an unfavourable course of disease not responsive to other established immunotherapies [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated therapeutic efficacy in the treatment of a wide range of solid tumours, such as breast cancer, and haematological malignancies [1]. Based on beneficial results from the experimental allergic encephalomyelitis (EAE) animal model of multiple sclerosis (MS), where mitoxantrone suppressed relapses and lesions 10–20 times more effectively than cyclophosphamide [5, 6, 7], pilot studies showed positive effects on relapse and progression rate in heterogeneous groups of patients who had an unfavourable course of disease not responsive to other established immunotherapies [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, it has also been proposed that anthracenedione drugs containing side chain amine groups can induce apoptosis in cancer cells through formation of a covalent adduct with the N-2 amino group of a guanine residue at CpG sites after activation by formaldehyde. [14][15][16] The results of this study confirm that daunorubicin, mitoxantrone and pixantrone can form covalent adducts with duplex DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increasing temperature is likely to result in the decreased stability of the complex, and thus lowers the value of the static quenching constant. 34,35 In order to test this view, the fluorescence quenching data were analyzed by the well-known Stern-Volmer Eq. (1).…”
Section: The Quenching Mechanismmentioning
confidence: 99%